Farmers’ Centric Indigenous Duckling Production Technology in North and Middle Andaman, India - Tamilvanan, Sujatha; Kundu, Anandamoy; Sunder , Jai; Lal, Shardul (International Journal of Livestock Research, 2019)
Need based programme and the concept of “Through farmers to farmers’’ was planned and executed to address the issue of non-availability of ducklings in N&M Andaman. The concept empowered farmers to produce more ducklings through the scientific native duck farming with pond based elevated housing, balanced feeding and artificial incubation using community based mini incubator. In the present study, age of sexual maturity of 190.0±10.0 days, average body weight of 1290.0±40.0 grams at 14 weeks of age, annual egg production/duck of 195.0±5.0 numbers with an average egg weight of 61.0±1.5 grams and hatchability of 40.9±5.6 per cent in Andaman local duck were recorded under scavenging conditions. The results revealed a significant (p<0.05) increase in availability of ducklings. This concept disseminated farmers’ centric native duckling production technology of artificial incubation using mini incubator to the farmers in really remote areas of North and Middle Andaman and they sell ducklings @ Rs.35 per duckling.